(untitled) (Journal of Food and Dietetics Research, 2024)
Objectives: To design a Mediterranean diet (MD) that can be utilized as an intervention in a randomized controlled trial. Methods: Dietary components were proposed for a Mediterranean menu and typical Pakistani diet. Three-day menu cycles were arranged utilizing the laid-out dietary components. Recipes were created and adjusted to meet the menu objectives at the 2000 calorie level. Using this basic meal plan of 2000, we further developed meanu plans for other multiple menus to give a total of 2500, 3000, and 3500 kcal/day. Results: our results show that 100% of the grains in the Mediterranean meal plan are provided, while the typical Pakistan meal plan provided 10% of whole grain.nutrient-empty and energy-dense desserts and cakes were included for the typical Pakistani meal plan on a daily basis, while these were represented at the least by a MD meal plan. To compare the overall health promotion characteristic, the mean HEI score for the three-day menu cycle was 92.5 and 30.4 for the MD and the typical Pakistani meal plans, respectively, showing the MD diet is more superior in terms of overall health-promotion compared to the other diet plan. Results from the 10 pilot subjects show good compliance of eating their diet in accordance to MD dietary regimen. Mean HEI determined for genuine member consumption (n = 10, 6 days each) was: 92.5% and 30.4%, respectively, for the MD and typical Pakistani diet regimen.